Profitability Determinants of Kuwait Banking Industry: Comparative Analysis between Islamic and Conventional Banks - Abduh, Muhamad; Issa, Mohamed Saeed (Ekonomi Syariah IAIN Kudus, 2018)
This study is aimed at evaluating the impact bank specific and macroeconomic variables including the global financial crisis upon the performance of Islamic and conventional banks in Kuwait. The data are collected from nine banks operated in Kuwait over the period of 2005 to 2012 with four of them are Islamic banks and five are conventional banks. The ROA and ROE are used to measure profitability while the size, credit risk, bank diversification, efficiency, capital strength, and liquidity were used to measure bank specific variables. There are also three external variables that would be used to measure macroeconomic condition i.e. GDP growth, inflation, and financial crisis. The findings from pooled OLS have shown that credit risk, liquidity and efficiency significantly affecting profitability for both Islamic and conventional banks. For macroeconomic conditions, GDP is positively significantly affecting profitability of Islamic banking sector, while inflation is negatively affecting the profitability of conventional banking sector. The result also evidence that Islamic banking sector is more stable than the conventional banking sector in terms of their performance during and after the crisis period.